Midwives' decision-making process when a non-vigorous neonate is born – a Swedish qualitative interview study. (November 2022) - Isacson, Manuela; Andersson, Ola; Thies-Lagergren, Li
ABSTRACT: Objective: : Midwives are often the first ones to make decisions when a neonate is unexpectedly born non-vigorous. This study aimed to understand how midwives reason and what they experience when deciding what to do when a non-vigorous neonate is born. In present practice, the decision to cut the umbilical cord early is strongly affected bythe decision that the neonate needs resuscitation. To better understand the decisions taken during the first minutes of the non-vigorous neonate’s life, this study focused on the midwives’ decision to cut the umbilical cord. Design: : A qualitative study with an inductive and descriptive design using the Critical Incident Technique was chosen to gain a more in-depth understanding of the factors influencing the midwife’s decision-making process concerning cutting the umbilical cord in a critical situation. Semi-structured interviews were conducted, and thematic analysis, as described by Braun and Clarke, was performed. Setting and participants: : Eligible study participants were midwives currently working in labour wards in Sweden. Findings: : In total, 14 midwives were interviewed between November 2019 and March 2020. The interviews rendered an understanding about midwives' decision-making on the timing of cord clamping in the non-vigorous neonates. An overarching theme was generated: "The balancing act of clamping the umbilical cord" which consisted of three themes, "Assessing the neonate in need of resuscitation", "Valuing own knowledge and experience" and "Influencing decision-making", and seven sub-themes. Many factors in addition to clinical reasoning influenced the midwives' decision-making processes. Feelings, intuition, and experience also had an effect to varying degrees.